2016
DOI: 10.1002/cite.201600040
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐up of Dry Hopping Trials: Importance of Scale for Aroma and Taste Perceptions

Abstract: In this study beers that were dry hopped in three different batch sizes were compared. The hop-oil concentrations were measured and possible aroma-active hop volatiles were identified in the hop pellets as well as in the beers. The analytical results were correlated with the tasting results from a trained tasting panel. Mass transfer rates were not comparable between the different scales, and significant differences could be detected by the tasters. The beers dry hopped on an industrial scale are not comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 49 publications
3
27
0
1
Order By: Relevance
“…10 In a laboratory-scale experiment, also a decline in the myrcene concentration was observed between days 1 and 7. 32 In contrast, Wolfe et al showed almost constant concentrations of linalool and myrcene during a dry-hopping period of 7 days. 33 For all analysed esters, transfer rates up to 91%, referred to the concentrations in hops, were obtained during the first 2-3 days (Figure 2).…”
Section: Time Dependency Of the Transfer Of Odorants During Dry-hopmentioning
confidence: 91%
See 3 more Smart Citations
“…10 In a laboratory-scale experiment, also a decline in the myrcene concentration was observed between days 1 and 7. 32 In contrast, Wolfe et al showed almost constant concentrations of linalool and myrcene during a dry-hopping period of 7 days. 33 For all analysed esters, transfer rates up to 91%, referred to the concentrations in hops, were obtained during the first 2-3 days (Figure 2).…”
Section: Time Dependency Of the Transfer Of Odorants During Dry-hopmentioning
confidence: 91%
“…30,31 A quite similar course of the curve for linalool and geraniol was already shown for dry-hopped alcoholic beer in different production scales. 32 In a semi-industrial scale, a maximal transfer of linalool and geraniol in the first 24 hours and a slight decline of the concentrations in the following days were reported. 32 An increase of geraniol concentration at the end of the dry-hopping period can be attributed to the use of the hop variety Mandarina Bavaria, that has been shown to have high contents of geranyl acetate, acting as geraniol precursor.…”
Section: Time Dependency Of the Transfer Of Odorants During Dry-hopmentioning
confidence: 97%
See 2 more Smart Citations
“…The CO 2 produced during alcoholic fermentation also affects the decrease of aroma compound yields in beer. [5][6][7][8] To avoid the loss of aroma constituents and to achieve better yields dry hopping technique is in use, where hops are added at a later stages of brewing process, during fermentation or maturation.…”
Section: Introductionmentioning
confidence: 99%